Brain dysfunction in tubular and tubulointerstitial kidney diseases. (18th November 2021) - Viggiano, Davide; Bruchfeld, Annette; Carriazo, Sol; de Donato, Antonio; Endlich, Nicole; Ferreira, Ana Carina; Figurek, Andreja; Fouque, Denis; Franssen, Casper F M; Giannakou, Konstantinos; Goumenos, Dimitrios; Hoorn, Ewout J; et al.
ABSTRACT: Kidney function has two important elements: glomerular filtration and tubular function (secretion and reabsorption). A persistent decrease in glomerular filtration rate (GFR), with or without proteinuria, is diagnostic of chronic kidney disease (CKD). While glomerular injury or disease is a major cause of CKD and usually associated with proteinuria, predominant tubular injury, with or without tubulointerstitial disease, is typically non-proteinuric. CKD has been linked with cognitive impairment, but it is unclear how much this depends on a decreased GFR, altered tubular function or the presence of proteinuria. Since CKD is often accompanied by tubular and interstitial dysfunction, we explore here for the first time the potential role of the tubular and tubulointerstitial compartments in cognitive dysfunction. To help address this issue we selected a group of primary tubular diseases with preserved GFR in which to review the evidence for any association with brain dysfunction. Cognition, mood, neurosensory and motor disturbances are not well characterized in tubular diseases, possibly because they are subclinical and less prominent than other clinical manifestations. The available literature suggests that brain dysfunction in tubular and tubulointerstitial diseases is usually mild and is more often seen in disorders of water handling. Brain dysfunction may occur when severe electrolyte and water disorders in young children persist over a long period of time before the diagnosis is made. We have chosen Bartter and Gitelman syndromes and nephrogenic diabetes insipidus as examples to highlight this topic. We discuss current published findings, some unanswered questions and propose topics for future research.